1998
DOI: 10.1111/j.1600-0447.1998.tb10067.x
|View full text |Cite
|
Sign up to set email alerts
|

A 16‐year follow‐up study of schizophrenia and related disorders in Sofia, Bulgaria

Abstract: A total of 60 patients with functional non-affective psychoses were assessed 16 years after their inclusion in the WHO co-ordinated study on reduction and assessment of psychiatric disability. All patients at inclusion had a recent onset of a psychotic disorder. About one-third of the patients had a good outcome. The rest showed moderate to severe psychiatric symptoms and social disability. Comparison with other similar studies suggested that our results show a low mortality rate, high levels of clinical sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
1
13
1
3
Order By: Relevance
“…A more recent publication, which examined this finding in light of the ISOS reassessment of the original WHO studies cohort, also reported evidence of a better course of illness in developing countries (8). However, the authors discuss possible biases, especially those termed as cultural factors.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A more recent publication, which examined this finding in light of the ISOS reassessment of the original WHO studies cohort, also reported evidence of a better course of illness in developing countries (8). However, the authors discuss possible biases, especially those termed as cultural factors.…”
mentioning
confidence: 97%
“…More recently, the International Study of Schizophrenia (ISOS) reassessed the samples included in the original WHO studies, with follow-up periods ranging from 13 to 26 years. Field and coordinating centres have published data from these reassessments (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…D'altro canto questo problema non e di facile soluzione e con esso hanno dovuto fare i conti tutti coloro che, Epidemiologia e Psichiatria Sociale, 13, 3, 2004 anche in campo internazionale, sono stati impegnati in studi analoghi al nostro (Sartorius et al, 1996;Mason et al, 1996;Ganev et al, 1998;Harrison et al, 2001). Eravamo consapevoli di questo problema gia in fase di pianificazione dello studio; abbiamo tuttavia scelto di proposito l'adozione di tale strategia in quanto la valutazione al follow-up e stata effettuata su una quota ragguardevole di soggetti che non erano gia da tempo piu in carico al Servizio e che avrebbero potuto fornire informazioni relative alia loro storia clinica soltanto affidandosi alia propria memoria: chiedere informazioni riguardanti eventi troppo lontani nel tempo avrebbe rischiato di produrre dati non del tutto attendibili, introducendo di fatto il cosiddetto memory bias.…”
Section: Discussioneunclassified
“…Si tratta in realta di una questione nota da tempo: gia Bellack (1958) aveva segnalato che i criteri per la caratterizzazione deH'andamento dei disturbi mentali erano talmente vaghi da non poter essere utilizzati in maniera affidabile ai fini di una corretta classificazione del decorso; e d'altro canto, in un documento prodotto verso la meta degli anni '80 da un panel di esperti del National Institute of Mental Health statunitense (1988), era stato sottolineato come la conoscenza dei pattern di decorso della schizofrenia fosse incompleta e lacunosa, a causa della mancata disponibilita di procedure standardizzate per la codificazione delle caratteristiche di decorso. Bisogna giungere ai piu recenti sviluppi dei progetti collaborativi internazionali, realizzati sotto l'egida dell'OMS, perche la metodologia di studio sul decorso dei disturbi mentali cominci ad avvalersi del-1'utilizzo di strumenti standardizzati per la ricostruzione del decorso tali da fornire evidenze empiriche piu robuste e convincenti (Jablensky et al, 1992;Mason et al, 1996;Sartorius et al, 1996;Ganev, 1998;Wiersma et al, 1998;Harrison et al, 2001).…”
unclassified
“…Kraepelin believed that dementia praecox was marked by an inevitable downward course; individuals diagnosed with this disorder would never return to a state that would allow them to be contributing members of society. The early pessimistic predictions for recovery from schizophrenia were disputed by numerous longitudinal studies illustrating that people with schizophrenia were not necessarily resigned to a life of incompetence and institutionalization [8][9][10][11][12][13][14][15][16][17][18][19][20]. These studies were crossnational, completed in Japan, Germany, Switzerland, and the United States.…”
Section: Recovery As Outcomementioning
confidence: 98%